Engaging with Brecht Making Theatre in the Twenty-first Century - Gelber, Bill. (Cham : Springer Nature Switzerland : Imprint: Palgrave Macmillan, 2023)
This book makes the case for Bertolt Brecht's continued importance at a time when events of the 21st century cry out for a studied means of producing theatre for social change. Here is a unique step-by-step process for realizing Brecht's ways of working onstage using the 2015 Texas Tech University production of Brecht's Mother Courage and Her Children as a model for exploration. Particular Brecht concepts-the epic, Verfremdung, the Fabel, gestus, historicization, literarization, the "Not...but," Arrangement, and the Separation of the Elements-are explained and applied to scenes and plays. Brecht's complicated relationship with Konstantin Stanislavsky is also explored in relation to their separate views on acting. For theatrical practitioners and educators, this volume is a record of pedagogical engagement, an empirical study of Brecht's work in performance at a higher institution of learning using graduate and undergraduate students. Bill Gelber is a Professor of Theatre in Acting, Directing, and Pedagogy at Texas Tech University, USA. He has been published in the Brecht Yearbook, Communications of the International Brecht Society, Southern Theatre, Texas Theatre Journal, and Early Modern Literary Studies and was recently inducted into the Texas Tech Teaching Academy. .
1. Why Engage with Brecht? -- 2. Five productions of Mother Courage: 1941, 1949, 1950, 1951, and 2015 -- 3. Collaborative Analysis -- 4.The Design Team, Meta-theatricality, and Literarization -- 5. First Rehearsal: Tools for Actors, Status and Haltung -- 6. Rehearsing the Actors I: Arrangement -- 7. Rehearsing the Actors II: Moment-to-Moment -- 8. Rehearsing the Actors III: Playing the Events -- 9. Documenting the Work: The Model Book -- 10. Responses and Future Work.
Keywords: Performing arts; Theater; Theater -- Production and direction; Playwriting; Dramatists; Education in literature; Theatre and Performance Arts; Theatre Direction and Production; Playwrights and Playwriting; Literature and Pedagogy